Control of chemical reactor for consecutive reactions II - Drábek, Oldřich; Krejčí, Stanislav (Univerzita Pardubice, 1995)
The second part of our study deals with a simulation of the chemical reactor control using a self-tuning regulator. The behaviour of the control loop in the case of the disturbance in the set-point and in the manipulated variable has been investigated. Furthermore, the adaptability of the self-tuning regulator with the parameters changes has been checked.